The Effectiveness of Roundtable Technique to Teach Writing Descriptive Text for Students with LowSelf-Efficacy - Maja, Adi (The Explora, 2021)
Self efficacy is someone’s belief of his capability to complete a task or to perform something. Zimmerman and Martinez-Pons, as cited in Kitikanan and Sasimonton (2017: 4) say, “Students with high self-efficacy tend to learn and achieve more than those with low ones”. In other words, when someone has high self-efficacy, his/her effort to do writing will be better and it is assumed that their writing achievement will be better as well. On the contrary, students with low self-efficacy often have lower score of writing than the students with high self-efficacy. Then, many techniques work well for only students with high self-efficacy. This study was designed to see whether or not Roundtable technique is effective tobe used to teach writing descriptive text for the students with low self-efficacy. The research was done at SMA N 1Panyabungan. This was an experimental research design with 51 students in the population. The students were spread in three classes which consist of 17students in each class. Two classes were chosen as the sample by using cluster random sampling technique. One class was the experiment class, and the other was as control class. Students’ self-efficacy was tested by using questionnaires. Then, they were grouped into students with high and low self-efficacy. After that they were given treatment. The data were then collected after the treatment was given by administering writing test. The students’ writing achievement scores were analyzed by using t-test formula and the level of significance used was 0.05(5%).After being calculated, the value of t-observed was 2.975, whereas the t-table was 2.306. Consequently, Roundtable technique was effective to be used to teach the students with low selfefficacy to write descriptive text at Al Azhar Islamic Junior High School 32 Padang.